2016
DOI: 10.1073/pnas.1613701113
|View full text |Cite
|
Sign up to set email alerts
|

Complex I assembly into supercomplexes determines differential mitochondrial ROS production in neurons and astrocytes

Abstract: Neurons depend on oxidative phosphorylation for energy generation, whereas astrocytes do not, a distinctive feature that is essential for neurotransmission and neuronal survival. However, any link between these metabolic differences and the structural organization of the mitochondrial respiratory chain is unknown. Here, we investigated this issue and found that, in neurons, mitochondrial complex I is predominantly assembled into supercomplexes, whereas in astrocytes the abundance of free complex I is higher. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
290
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 344 publications
(316 citation statements)
references
References 53 publications
25
290
1
Order By: Relevance
“…Conversely, the assembly of mitochondrial Complex I into supercomplexes determines, for example, the differential production of reactive oxygen species in neurons and astrocytes [109]. Addressing specific sites of mitochondrial H 2 O 2 production may have therapeutic potential [110].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the assembly of mitochondrial Complex I into supercomplexes determines, for example, the differential production of reactive oxygen species in neurons and astrocytes [109]. Addressing specific sites of mitochondrial H 2 O 2 production may have therapeutic potential [110].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the alteration in CL molecular species in TAZ kd brain may contribute in part to the elevation in supercomplexes despite an overall decrease in long-chain unsaturated fatty acid containing CL species. Alternatively, the increase in total supercomplex content may reflect the differential assembly of supercomplexes in astrocytes and neurons 55 .…”
Section: Discussionmentioning
confidence: 99%
“…This enhanced resistance to oxidative damage in astrocytes is observed despite the fact that astrocytes have a deficient mitochondrial respiration and increased ROS formation when compared to neurons (Lopez-Fabuel et al 2016). A comparative study also demonstrated that astrocytes are more resistant to oxidative damage than microglia or oligodendrocytes (Hollensworth et al 2000).…”
Section: Mitochondrial Dysfunction In Glial Cells and Its Effect Omentioning
confidence: 99%